Taxonomic notes on Astragalus vogelii subsp. fatimensis (Galegeae, Fabaceae) - Punjani, Bhasker; Patel, Suresh; Desai, Prashant; Chaudhary, Lal Babu; Sanjappa, Munivenkatappa (Phytotaxa, 2021)
The correct authority of Astragalus vogelii subsp. fatimensis and its distribution range in India are discussed. The taxon, which is considered rare in India, has been recollected from Gujarat State from new localities in the Banaskantha District. The description of the taxon along with photographs and other taxonomic details are provided here for easy identification.